2011
DOI: 10.1042/cs20110178
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and reoxygenation modulate the arrhythmogenic activity of the pulmonary vein and atrium

Abstract: Ischaemia and reperfusion contribute to the genesis of AF (atrial fibrillation). PVs (pulmonary veins) and the atria are important foci for AF initiation and maintenance. However, the effect of ischaemia and reperfusion on PVs and the atria has not yet been fully elucidated. In the present study, conventional microelectrodes were used to record the APs (action potentials) in isolated rabbit PV, LA (left atrium) and RA (right atrium) specimens during hypoxia and reoxygenation, and pharmacological interventions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 38 publications
1
40
0
2
Order By: Relevance
“…[304,305]. Do występowania AF u pacjentów z obturacyjnym bezdechem sennym może się przyczyniać wiele mechanizmów patofizjologicznych, w tym dysfunkcja autonomiczna, hipoksja, hiperkapnia oraz zapalenie [96,[304][305][306][307]. Obturacyjny bezdech senny nasila zmiany ciśnienia wewnątrz klatki piersiowej, które same oraz za pośrednictwem aktywacji nerwu błędnego mogą prowadzić do skrócenia potencjału czynnościowego w przedsionkach i wywoływać AF.…”
Section: Ablacja Przezcewnikowa U Otyłych Pacjentówunclassified
“…[304,305]. Do występowania AF u pacjentów z obturacyjnym bezdechem sennym może się przyczyniać wiele mechanizmów patofizjologicznych, w tym dysfunkcja autonomiczna, hipoksja, hiperkapnia oraz zapalenie [96,[304][305][306][307]. Obturacyjny bezdech senny nasila zmiany ciśnienia wewnątrz klatki piersiowej, które same oraz za pośrednictwem aktywacji nerwu błędnego mogą prowadzić do skrócenia potencjału czynnościowego w przedsionkach i wywoływać AF.…”
Section: Ablacja Przezcewnikowa U Otyłych Pacjentówunclassified
“…Hypoxia could do damage to cell function and induce EADs in myocardial cells (47). Previous studies showed that RAN suppressed EADs induced by many pathological conditions, such as ATXa, veratridine, and H 2 O 2 (37,48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Sino et al 8 demonstrated that a 3–5-hour regional acute right atrial ischemia associates with an increased burst pacing-induced AF duration, and regional impairment in conduction. Lin et al 19 suggested that a 60-minute global atrial hypoxia leads to a shorter pulmonary vein APD and an increased number of early and delayed after-depolarizations. Also, Jayachandran et al showed that a 15-minute atrio-ventricular ischemia, obtained after right coronary ligation, leads to a right atrial APD shortening prevented by a Na/H exchanger blocker, HOE642.…”
Section: Discussionmentioning
confidence: 99%